Advances in taxation. Vol. 20 - Stock, Toby, 1961- (Advances in taxation,, 2012)
The eight articles in the volume include three articles on tax compliance and related topics. Specifically, Chambers and Curatola examine whether greater tax payment frequency improves compliance and decreases delinquencies. Gemmell and Hasseldine discuss and analyze the state of the "tax gap" literature. MacGregor and Wilkinson investigate the effect of economic patriotism on taxpayer compliance attitudes. Volume 20 also includes two articles on federal tax issues. Addy and Yoder investigate factors associated with private foundations that narrowly fail a test that would reduce the tax the foundation pays on investment income. Liedtka and Nayar examine the motivation for early exercise of certain stock options. Two articles in this volume examine state tax issues. Jalbert and Fleischman analyze interactions between federal section 179 deduction decisions and Hawaiian tax credit elections. Key investigates the effect of one county's property tax policy decisions on those of adjoining counties. Last but not least, one paper deals with practitioner information search. Cloyd, Spilker and Wood investigate how supervisors can affect the information search behavior of their subordinate practitioners.